Design and implementation of a dynamic FPAA based photovoltaic emulator. (January 2016) - Balato, Marco; Costanzo, Luigi; Gallo, Daniele; Landi, Carmine; Luiso, Mario; Vitelli, Massimo
Highlights: Photovoltaic emulator based on a Field Programmable Analog Array. The FPAA provides a reference for the output current control of a DC/DC converter. The output port of the DC/DC converter emulates the photovoltaic I – V curve. The emulator allows to track time varying irradiance values. No interpolations and no storage of data, great ease of reconfiguration of FPAA. Abstract: In this paper, a new Photovoltaic (PV) emulator is presented and discussed. Its main feature is represented by the use of a Field Programmable Analog Array (FPAA) on which the desired current vs. voltage ( I – V ) PV characteristic can be implemented. The FPAA provides a suitable analog time varying reference signal for the output current control of a proper DC/DC converter whose output port emulates the PV I – V curve. The proposed emulator allows to track time varying irradiance values and therefore it allows also to emulate typical scenarios of automotive applications or involving fast time varying weather conditions (e.g. the ones which usually occur in tropical locations). Additional, not less important advantages of the proposed solution are the following ones: (1) no numerical interpolations and no storage of big amount of data in memory are required; (2) the FPAA is characterized by a great ease of reconfiguration and programming with respect to FPGA or DSP based implementations; (3) no DAC or ADC converters are needed; (4) not only uniform but also mismatching operating conditions can be easily emulated; (5) power sources different from PV sources can be easily emulated by using the same architecture. The presented experimental results allow to confirm the validity of the proposed FPAA based architecture.